(3JMaI Phj GdYQaGf aj ehdO SjO Hfj YOfGfs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj aJM CbaGd gPG GdYGde HeaJGM XghQ SjO GdSGOGJ hLYd CeJg hSWG haVdgG Ydi SGFQ GdCee aj GdYHGOGJs
(3BNQgG (B:s
(3gd Pj YQhS bO HOJ (B*** (3aj MSfgG JSHj GdCfGe , Ce ZUf HGf CbHdJ (B*** (3JHOj dfG CMdi GHJSGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs